Science in times of crisis: How does the war affect the efficiency of Ukrainian scientists? - Suchikova, Yana; Tsybuliak, Natalia; Lopatina, Hanna; Shevchenko, Liudmyla; Popov, Anatoli I. (Business Perspectives, 2023)
This study aims to assess how to prevent the loss of academic potential due to the full-scale war unleashed by Russia on the territory of Ukraine. The paper establishes the relationship between the location of Ukrainian researchers and their ability to engage in scientific activity and determines the factors that decrease scientific efficiency during the war. Moreover, it identifies the influence of the scientists’ place of residence on their scientific efficiency. The sample comprises 172 lecturers from Berdyansk State Pedagogical University, Ukraine. This university was chosen because it was located in the temporarily occupied territory at the beginning of the war and later was relocated to another city. 40.8% of respondents who left the temporarily occupied territory for the Ukraine-controlled territories noted a decrease in the effectiveness of their scientific activities. Furthermore, 33.8% could not think about science at all. The most challenging situation is for those who went abroad: 55.6% show decreased scientific activity, and 27.7% note its complete absence. The most significant reasons that prevent scientific activity are financial instability, lack of access to equipment, loss of relevance of previously started research, inability to concentrate on science, poor quality or lack of Internet, and adaptation to a new residence.--//-- This is an open access article Yana Suchikova, Natalia Tsybuliak, Hanna Lopatina, Liudmyla Shevchenko and Anatoli I. Popov (2023). Science in times of crisis: How does the war affect the efficiency of Ukrainian scientists?. Problems and Perspectives in Management, 21(1), 408-424. doi:10.21511/ppm.21(1).2023.35 published under the CC BY 4.0 licence.
Keywords: scientific efficiency; scientific activity; crisis; large-scale war; university; temporarily occupied territory; Research Subject Categories::SOCIAL SCIENCES